Chromatin-based reprogramming of a courtship regulator by concurrent pheromone perception and hormone signaling - Zhao, Songhui (Sci Adv, 2020)
To increase fitness, animals use both internal and external states to coordinate reproductive behaviors. The molecular mechanisms underlying this coordination remain unknown. Here, we focused on pheromone-sensing Drosophila Or47b neurons, which exhibit age- and social experience–dependent increase in pheromone responses and courtship advantage in males. Fruitless(M) (Fru(M)), a master regulator of male courtship behaviors, drives the effects of social experience and age on Or47b neuron responses and function. We show that simultaneous exposure to social experience and age-specific juvenile hormone (JH) induces chromatin-based reprogramming of fru(M) expression in Or47b neurons. Group housing and JH signaling increase fru(M) expression in Or47b neurons and active chromatin marks at fru(M) promoter. Conversely, social isolation or loss of JH signaling decreases fru(M) expression and increases repressive marks around fru(M) promoter. Our results suggest that fru(M) promoter integrates coincident hormone and pheromone signals driving chromatin-based changes in expression and ultimately neuronal and behavioral plasticity.